2006
DOI: 10.1021/la0615894
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Supramolecular Assembly of Redox-Active Dendrimers at Molecular Printboards by Scanning Electrochemical Microscopy

Abstract: Redox-active ferrocenyl (Fc)-functionalized poly(propylenimine) (PPI) dendrimers solubilized in aqueous media by complexation of the Fc end groups with beta-cyclodextrin (betaCD) were immobilized at monolayers of betaCD on glass ("molecular printboards") via multiple host-guest interactions. The directed immobilization of the third-generation dendrimer-betaCD assembly G3-PPI-(Fc)16-(betaCD)16 at the printboard was achieved by supramolecular microcontact printing. The redox activity of the patterned dendrimers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 62 publications
2
52
0
Order By: Relevance
“…24,16 The resulting electrode surfaces were washed by dipping them in gently stirred clean buffer solutions.…”
Section: Duringmentioning
confidence: 99%
“…24,16 The resulting electrode surfaces were washed by dipping them in gently stirred clean buffer solutions.…”
Section: Duringmentioning
confidence: 99%
“…A cyclic voltammogram (Figure 3) recorded at a 25 µm diameter Pt microelectrode presents the classical sigmoidal shape characteristic of microelectrodes where the steady state current, i ss , is directly related to the bulk concentration of FcMeOH in solution. Finally, the use of FcMeOH in the fabrication of ferrocenyl-functionalized poly(propylenimine) (PPI) dendrimers (16) was also an encouraging parallel study that suggested that FcMeOH might be amenable to surface functionalization of liposomes. In enzymatic-assisted synthesis, it is important to control the parameters related to the enzyme activity, such as the enzyme strain, environment and reaction temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The study of Nunez et al [250] on the rheological behavior of hb polyesters and their blends with linear polymers observed a drastic decrease in viscosity depending on the hb polymer concentration in the blends. More recently, Li et al [251] employed hb poly(ether ether ketone) (hb-PEEK) at 1-5 wt% as a rheology modifier towards linear poly(ether ether ketone) (LPEEK) for improving the melt processability.…”
Section: Additives and Rheology Modifiermentioning
confidence: 98%